The Culture of Society’s Ritual To Lotang In Watang Bacukiki, Parepare City - Hj. St. Aminah; Abdul Jalil (Journal of Research and Multidisciplinary, 2019)
The values ​​of local cultural education in the Tau Lotang teachings of the Wattang Bacukiki community in the City of Parepare are inspired by the custom called 'urf, which is the custom of the local people for generations. The Dimension urf which is an element of the local culture of the community has monotheistic values, human values, life values, spiritual values, moral values, social values ​​and intellectual values, as an integration of multicultural education which is oriented to strengthening the values ​​of Nusantara Islamic education in the context to Indonesia. Along with the times, the community Tau Lotang has grown and interacted with other communities. But now many are in other jobs. At present, the profession of descendants of To Lotang is no longer just farming but there are already police, civil servants, nurses and various other professions. Even so, they still maintain their traditions as an integral part of local culture, especially the ritual traditions of the tomb loang loma and mappalili.